Introduction to Cloud Computing (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The Cloud computing is a fastest growing area in IT industry, computing and research industry. Cloud is a pool of virtualized computer resources .A cloud can support self-redundant, self-recovering and scalable programming models that allow data to recover from any hardware/software failures. With the advent of this new technology, you can access the data online if you have an access to the internet. The intent of this paper is to have a review on cloud computing, how it works, services of cloud computing and its deployment models, benefits and challenges.